THE DYNAMICS OF RECIPROCAL SELECTIVE SWEEPS OF HOST RESISTANCE AND A PARASITE COUNTER‐ADAPTATION IN DROSOPHILA. (16th November 2012) - Wilfert, Lena; Jiggins, Francis M.
Abstract : Host–parasite coevolution can result in consecutive selective sweeps of host resistance alleles and parasite counter‐adaptations. To illustrate the dynamics of this important but little studied form of coevolution, we have modeled an ongoing arms race between Drosophila melanogaster and the vertically transmitted sigma virus, using parameters we estimated in the field. We integrate these results with previous work showing that the spread of a resistance allele of the ref(2)P gene in the host was followed by the spread of a virus genotype, which overcomes this resistance. In line with these observations, our model predicts that there can be rapid selective sweeps in both the host and parasite, which can drive large changes in the prevalence of infection. The virus will tend to be ahead in the arms race, as incomplete dominance slows down host adaptation and selection for host resistance is weaker than selection for parasites to overcome resistance—the "life‐dinner" principle. This asymmetry in the adaptation rates results in a partial sweep of the host resistance allele, as it loses its advantage part way through the selective sweep. This well‐understood natural system illustrates how the outcome of host–parasite coevolution is determined by different population genetic parameters in the field.